Three-dimensional (3D) α-Fe2O3/polypyrrole (PPy) nanocomposite for effective electromagnetic absorption - Jiang, Wanchun; Sun, Mengxiao; Zhang, Kun; Wu, Fan; Xie, Aming; Wang, Mingyang (AIP advances, 2016)
The lightweight and 3-dimensional reticulated α-Fe2O3/PPy hybrids were successfully fabricated via a facile one-pot polyreaction. The measured complex permittivity and microwave attenuation performance suggest that the dielectric properties of PPy can be regulated by the mass ratio of added α-Fe2O3. The two dielectric resonance peaks of complex permittivity can be ascribed to the interface capacitor-like structure. An equivalent circuit model was established to explain the nonlinear resonance behavior of the α-Fe2O3/PPy wax composites. The addition of α-Fe2O3 properly tuned the dielectric constant to endow the composites with highly efficient microwave absorption. The minimum reflection loss of α-Fe2O3/PPy wax composites were enhanced to nearly −29dB with an effective bandwidth (RL≤ − 10dB) up to 5.0GHz. The numerical method was proposed to calculate the optimum thickness for minimum RL at expected frequency by detailed investigation on the transmission formula. Moreover, the required thickness for optimum absorption efficiency at expected frequency can be obtained directly.